If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + -4) + 2 = 2 Reorder the terms: 2(-4 + a) + 2 = 2 (-4 * 2 + a * 2) + 2 = 2 (-8 + 2a) + 2 = 2 Reorder the terms: -8 + 2 + 2a = 2 Combine like terms: -8 + 2 = -6 -6 + 2a = 2 Solving -6 + 2a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2a = 2 + 6 Combine like terms: -6 + 6 = 0 0 + 2a = 2 + 6 2a = 2 + 6 Combine like terms: 2 + 6 = 8 2a = 8 Divide each side by '2'. a = 4 Simplifying a = 4
| 6-9n=7n-9n+13 | | 5(2x-7)=20x-10-5x | | 3(20)+35=4(20)+15 | | 2+(-v)=15 | | 84+2x=4x(12+x) | | 39+1x=15+3x | | 90+x=210 | | 4x-7=10x+11 | | 8x-10=59 | | 15+1x=8+2x | | 4x+10=2x-2 | | y=x^2+4x-45 | | -12y=-60 | | 4(2-3x)=-2(x-5) | | y=-.4(-10)+1 | | 3x+2(4x-3)=83 | | 7n^2+17r+6=0 | | ln^3x=0 | | 4x-2(6-3x)=100 | | -3(6x-8)+1=-18x+25 | | 12-h=24 | | 14-2(3p+1)=(4+p) | | 3x(7x-20)=96 | | 14-2(3p+1)=4+p | | 6(m-2)=45 | | 155+3x^2=20 | | -98=-7(2+2b) | | 2(x+13)+1=1-3(10-x) | | 5(1-3v)=-100 | | 4x^2+0.3=0 | | -12times-14= | | n+6=3+7+n-2n |